Urgensi Aspek Gramatika dalam Wacana Lisan Bahasa Inggris - Saefuddin Saefuddin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
Oral Communicative competency in English is need to provide the initation into subcultures, occupations,professions, socialisations and dicipline enquiry. To speak one anonther, we make use of sentences, or, to be morepractice, utterance. Such utterances can be performed in anyone of variaty ways, but to those who believe that shorterutterances are more easy understood than longer ones. That is why an utterance can be expressed in merely one phrasedor sentence. Controvercies among those who decide whether or not grammaar is needed for students to learn particularyin speaking skill bring us to attempt to analyzing how gramatical aspects such as morphem and syntax have morecontribution in the functional sentences (pragmatic). Therefore, to teach how to perform language functions and grammarmight not be separated: students need to learn grammar but they also need to be taught functions. The decision is obvious:depending which levels we are talking about. In other word we need to consder those levels, such as level of difficulty,the level of transparency, and the level of formality.